2010
DOI: 10.1111/j.1440-1789.2010.01105.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased ratio of vascular endothelial growth factor to semaphorin3A is a negative prognostic factor in human meningiomas

Abstract: Semaphorin3A (SEMA3A) is an anti-angiogenic factor which is expressed in human meningiomas in association with low microvessel density (MVD). It competes with vascular endothelial growth factor (VEGF) for receptor neuropilin-1 (NRP-1). The ratio between VEGF and SEMA3A has been recently demonstrated to regulate neo-angiogenesis, proliferation and progression of tumors. To clarify the involvement of these proteins in the above-mentioned phenomena, we analyzed the immunohistochemical expression of SEMA3A, VEGF a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
21
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 44 publications
4
21
0
Order By: Relevance
“…The elevated levels of VEGF seen in this study confirm earlier reports not only on benign meningiomas, but atypical and malignant ones as well (40). It has been suggested that the increased ratio of the pro-angiogenesis factor VEGF to the anti-angiogenic factor SEMASA (which is expressed in human meningiomas association with low microvessel density) is a negative predictor of recurrence in these neoplasms (41). EMMPRIN, the extracellular MMP inducer, was also very highly expressed in all the meningiomas.…”
Section: Discussionsupporting
confidence: 80%
“…The elevated levels of VEGF seen in this study confirm earlier reports not only on benign meningiomas, but atypical and malignant ones as well (40). It has been suggested that the increased ratio of the pro-angiogenesis factor VEGF to the anti-angiogenic factor SEMASA (which is expressed in human meningiomas association with low microvessel density) is a negative predictor of recurrence in these neoplasms (41). EMMPRIN, the extracellular MMP inducer, was also very highly expressed in all the meningiomas.…”
Section: Discussionsupporting
confidence: 80%
“…120 Sema3A also functions as a potent inhibitor of angiogenesis and tumor progression in many types of solid tumors. Down-regulation of sema3A expression in tumor cells promotes tumor angiogenesis and tumor progression in many types of solid tumors [121][122][123][124][125][125][126][127] suggesting that it functions as an endogenous negative regulator of the angiogenic switch. 128 Prolonged stimulation of endothelial cells with sema3A induces apoptosis of endothelial cells suggesting that induction of apoptosis is a part of the mechanism by which it inhibits angiogenesis.…”
Section: Semaphorins As Regulators Of Tumor Progressionmentioning
confidence: 99%
“…1,25,51,52 Semaphorin3A (SEMA3A) is a negative regulator of neoangiogenesis, the formation of blood vessels from endothelial progenitors. 53,54 A high concentration of intra-tumoral neoangiogenesis, indicated by a high microvessel density (MVD), is significantly correlated with shorter overall survival and decreased recurrence-free survival. [54][55][56][57] High VEGF/SEMA3A ratio is strongly associated with an increase in recurrence, proliferation index, and higher histological grades, 54 as grade III meningiomas demonstrate a 10-fold increase in VEGF-A relative to benign meningiomas.…”
Section: Prognostic Factorsmentioning
confidence: 99%